Coronary Artery Aneurysm - Two Case Reports (Journal of Medicine, 2016)
Coronary aneurysms are defined as a localized dilatation that exceeds 1.5 times the diameter of the adjacent segment of artery. Aneurysms can be saccular (transverse larger than the longitudinal axis) or fusiform (longitudinal at least twice the transverse axis). These should be distinguished from coronary artery ectasia in which there is diffuse dilatation involving greater than 50% of the coronary arteryJ MEDICINE July 2016; 17 (2) : 111-114